Manfaat Penggunaan Biaya Kualitas terhadap Profitabilitas Perusahaan - Rokhmat, Nurhayat; Ramadhanty, Nadine; Sariah, Sariah; R Pandin, Maria Yovita; Riyadi, Slamet (JPNM Jurnal Pustaka Nusantara Multidisiplin, 2023)
Quality is a critical dimension in business competition that influences a company's competitiveness. Quality costs, including production and defect repair, play an important role in product quality control. High quality can increase market share and sales value, as well as reduce costs, thereby increasing company profitability. Based on this phenomenon, researchers conducted a meta-analysis based on research objectives, variables, research objects, research population/sample, data collection techniques, and analytical tools used.This research aims to determine and develop research regarding quality and profitability cost models. This research uses a meta-analysis method. Meta analysis is a review of a number of research results on similar problems. The unit of analysis in the research is written documents about quality cost model research in the form of journal articles based on their suitability to the research theme. The data analysis used is quantitative data analysis with percentages and qualitative data analysis for data resulting from descriptive analysis of 20 studies related to the effect of quality costs on profitability. The findings of the meta-analysis results based on research objectives, research variables used, research population/sample, data collection techniques and analysis tools show that the quality cost model categories can contribute to evaluating the optimization of quality achievements